Methadone Therapy in Underserved Urban Community: QTc Prolongation and Life‐Threatening Ventricular Arrhythmias. Issue 3 (June 2015) - Chowdhury, Mohsin; Wong, Jason; Cheng, Angela; Khilkin, Michael; Palma, Eugen
Summary Aims Methadone has been associated with QTc prolongation and ventricular arrhythmias but the prevalence of QTc prolongation and association with ventricular arrhythmias remains unclear. We investigated this in our inner city urban community (Bronx, New York) that has a large number of patients on methadone. Methods Telemetry records, nursing documentation and electronic charts of 291 patients spanning856 encounters were evaluated. QT was manually measured from ECG utilizing standardized QT measurement guidelines and was corrected for heart rate using Hodges formula. QTc >470 ms in males and >480 ms in females was considered to be prolonged. Results Patients had prolonged QTc, QTc >500 ms and ventricular arrhythmias during 25.6%, 14.1% and 3.4% of encounters, respectively. There was a very weak dose dependent relationship between methadone dose and QTc (Spearman's rho = 0.09).In addition to methadone, patients were on at least one QT prolonging drugs during 39% of the encounters. Patients who were receiving two interacting drugs in addition to methadone had the highest prevalence (29%) of QTc prolongation. Conclusion Although the prevalence of QTc prolongation among patients on methadone therapy is high, the prevalence of ventricular arrhythmia is relatively low. Hospitalized patients on sustained methadone therapy are frequently on multiple additional QTc prolonging drugs. There is no significant dose dependent relationship between methadone dose and QTc. However, the concurrent use of methadone and interacting drugs lead to an increased prevalence of QTc prolongation.